Design and verification of individualized follow-up strategy of colonoscopy for postoperative patients with colorectal cancer. Issue 1 (January 2022) - Guo, Chunmei; Wu, Jing; Jiao, Yue; Zhang, Qian; Wang, Canghai; Wang, Yadan; Liu, Hong; Zhang, Shutian; Wei, Nan; Lin, Wu; Liu, Kuiliang; Shi, Haiyun
Abstract : Background: Current guidelines do not establish an individual scheme for surveillance colonoscopy in postoperative colorectal cancer (CRC) patients. Aims: The purpose of the study was to screen possible risk factors for the development of metachronous adenoma in postoperative CRC patients and to develop a risk prediction model and verify it. Methods: Consecutive postoperative patients with CRC were enrolled from April 2007 to December 2013 as the derivation group. Baseline data of patients and clinicopathological features of the tumor were collected, logistic regression analysis was performed, and clinical model was established and was verified internally. The model was externally validated in an independent cohort (validation group) from January 2014 to October 2017 in the same hospital. Results: A total of 734 patients were included, with average (64.6 ± 11.5) years old. The overall incidence of metachronous adenoma was 35.4%. There was no significant difference in the incidence of metachronous adenoma between the derivation group and validation group ( P  > 0.05). Age, diabetes mellitus, right colon cancer, moderately to poorly differentiated adenocarcinoma and synchronous adenoma were independent risk factors for metachronous adenoma. The C-index of the metachronous adenoma line chart model was 0.932, and the index decreased by 0.022 after internal verification. The C-index of external validation was 0.910. The Hosmer–Lemeshow test showed that the P value of metachronous adenoma risk prediction model was 0.247. Conclusions: Individual surveillance strategies should be designed for postoperative patients with CRC. For high-risk patients, it is appropriate to undergo more than two colonoscopies in 36 months after operation.